Primary and Secondary Education in Morocco: From Access to School into Generalization to Dropout - Zoulal Mansouri; Mohamed El Amine Moumine (International Journal of Evaluation and Research in Education (IJERE), 2017)
This article provides an overview of school wastage, namely repetition and dropout in primary and secondary schools in Morocco. It describes how this phenomenon has progressed since school was implemented in the 1960s. It shows that the fundamental principles of the education system established in the aftermath of Morocco’s independence in 1956 did not succeed in providing a clear, stable education program. The article concludes that despite the tremendous efforts made in enrollment, school wastage persists, and the educational system is still trapped in the idealistic principles of the 1960s, causing education to flounder in the dramatic triangle of schooling, generalization, and dropout.